South Africa is in need of God’s Wisdom : Reading 1 Corinthians and James - Cornelius, Elma M (Stellenbosch Theological Journal, 2023)
In 2022, South Africa’s president was accused of corruption (Bloomberg, 2022). South Africa is in a deep political crisis and urgently in need of solutions as South Africans have had enough of the incompetence, indecency and selfishness that defines the leadership of the country (Brkic 2022). Theft, corruption, violence, murder, and other forms of crime in South Africa play a role in the crisis. Sociologist Heinecken (2020) says that violence is facilitated by lawlessness, corruption of the justice system, police brutality, and “an ideology that embraces … the use of violence as normal and desirable”. Psychologist Samenow (2022) says crime results from people’s thinking patterns. South Africa thus needs new thinking patterns. In 2012 (News24), former president Zuma acknowledged that South Africa needs wisdom. In 2016, after the “Save SA March”, SA religious leaders prayed inter alia for wisdom for South Africa (News24Wire 2016). South Africa is in dire need of wisdom. Wisdom is an attribute of God, and all human wisdom originates from God as His wisdom is a communicable attribute. Paul’s first letter to the Corinthians is addressed to a Christian church in Corinth with unique challenges in their community and Paul was angry with the Corinthians for clinging on to human wisdom and clinging on to immorality and conflict and disputes. In an argument in the letter-opening, Christ is presented by Paul as the wisdom of God. Paul states a contrast between human wisdom and the cross of Christ, between worldly patterns and the Christian message. What does God’s wisdom look like? James 3:17–18 gives seven characteristics of God’s wisdom: pure, peace-loving, considerate, submissive, full of mercy and good fruit, impartial and sincere. This article offers a reading of 1 Corinthians and James with a focus on God’s attribute of wisdom and how wisdom from God can benefit South Africans.